2016
DOI: 10.23939/chcht10.04.451
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Micro- and Macro-Cristalline Paraffins on the Physical and Rheological Properties of Crude Oil and Organic Solvents

Abstract: Abstract. The influence of micro-and macro-crystalline paraffins on the properties of crude oil and organic solvents was investigated. Micro-cristalline paraffins promote the most pronounced changes in the investigated physical and rheological properties of all tested solutions. The concentration of branched-alkanes in paraffins is the pivotal parameter that promotes these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Macro-and micro-crystalline waxes have different functional properties (including viscosity and melting point) due to the differences in their hydrocarbon content (linear or branched). Oliveira et al [35] investigated the influence of micro-and macro-crystalline paraffin on the properties of crude oil and found that Mic-wax can be dissolved or dispersed in solvents and display a sharp transition of gel-strength. The micro-crystalline wax usually crystallizes at a higher temperature compare to macro-components where stronger gels are formed.…”
Section: Composition and Characterization Of Waxy Crude Oilmentioning
confidence: 99%
See 1 more Smart Citation
“…Macro-and micro-crystalline waxes have different functional properties (including viscosity and melting point) due to the differences in their hydrocarbon content (linear or branched). Oliveira et al [35] investigated the influence of micro-and macro-crystalline paraffin on the properties of crude oil and found that Mic-wax can be dissolved or dispersed in solvents and display a sharp transition of gel-strength. The micro-crystalline wax usually crystallizes at a higher temperature compare to macro-components where stronger gels are formed.…”
Section: Composition and Characterization Of Waxy Crude Oilmentioning
confidence: 99%
“…The impact of micro-and macro-crystalline paraffin on the characteristics of crude oil and organic solvents. Adapted with permission from[35], Lviv Polytechnic, 2005.…”
mentioning
confidence: 99%
“…In general, waxy crude oils contain mainly nparaffins and small amounts of branched and cyclic paraffins. However, some crudes contain n-paraffins in small quantities relative to branched and cyclic paraffins 15 . The latter ones have a high pour point, which causes a deterioration in the rheological (mobility, fluidity, etc.)…”
Section: Introductionmentioning
confidence: 99%